2022
DOI: 10.1038/s41388-022-02563-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mutant versions of the R-RAS2/TC21 GTPase found in tumors

Abstract: The R-RAS2 GTP hydrolase (GTPase) (also known as TC21) has been traditionally considered quite similar to classical RAS proteins at the regulatory and signaling levels. Recently, a long-tail hotspot mutation targeting the R-RAS2/TC21 Gln72 residue (Q72L) was identified as a potent oncogenic driver. Additional point mutations were also found in other tumors at low frequencies. Despite this, little information is available regarding the transforming role of these mutant versions and their relevance for the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…It has recently been shown that endogenous R-RAS2 (upon R-RAS2 knock-out and knock-in of fluorescently labelled R-RAS2), unlike canonical Ras proteins, specifically localizes in focal adhesions [ 12 ]. However, in our experiments we did not observe that the sponge or the human homolog localizes in focal adhesions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been shown that endogenous R-RAS2 (upon R-RAS2 knock-out and knock-in of fluorescently labelled R-RAS2), unlike canonical Ras proteins, specifically localizes in focal adhesions [ 12 ]. However, in our experiments we did not observe that the sponge or the human homolog localizes in focal adhesions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in contrast to previous reports using ectopic expression systems that showed subcellular localization of R-RAS2 protein in the plasma membrane, Golgi apparatus, or endoplasmic reticulum [ 9 , 10 ], a recent study showed that endogenous wild-type R-RAS2 protein is specifically localized in both nascent and mature focal adhesions. The distribution of R-RAS2 overlaps with the focal adhesion marker vinculin and with F-actin present in these structures and regulates focal adhesion- and invasion-related functions [ 12 ]. This is in line with previous detection of R-RAS2 in proteomics experiments in myosin II-responsive focal adhesion complexes [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RRAS2, a member of the R-Ras subfamily of Ras-like low-molecular-weight GTPases, is located in the plasma membrane and functions as a signal transducer. Like other RAS proteins, it is considered to regulate cell proliferation and differentiation via the RAS/MAPK cascade, and somatic mutations in the RRAS2 gene are drivers of tumorigenesis; they have been detected in various tumors such as colon, lung, and skin cancers ( Aoki et al, 2016 ; Clavaín et al, 2023 ). Furthermore, germline RRAS2 mutations have been reported to cause NS ( Capri et al, 2019 ; Niihori et al, 2019 ; Weinstock and Sadler, 2022 ; Yu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other mutations (G23V/A/C/S, G24D/C/V, A70T, and Q72H) in human cancer have shown transforming potential when expressed in immortal cell lines [42].…”
Section: Introductionmentioning
confidence: 99%